STATISTICAL PROCESSING OF THE METEOROLOGICAL DATA FOR CONCLUSION ON THE PRESENCE OF THE TIME TRENDS - V. S. Mukha (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The technic of the processing of the meteorological data for conclusion on the presence of the time trends in the quantitative characteristics of the weather on the example of the analysis of the average yearly atmospheric temperature change at the meteorological station Minsk from 1989 is presented. The average yearly atmospheric temperature received from the measurements is approximated by the least square error method in the linear time dependence regression function. The linear time dependence regression function received in such a way has some positive growing (positive trend). The aim of this paper is to clarify the significance of this growth. For this aim, the usage of the regression analysis with its procedures of hypotheses testing is proposed. First of all, the performing of the demands presented to the regression analysis is checked: normality of the distribution of the disturbance and the homogeneity of the variance (dispersion) of the disturbance. The normality of the distribution of the disturbance was checked and confirmed by the Kolmogorov test. The homogeneity of the dispersion of the disturbance was checked and confirmed both by checking the hypotheses on the equality of the dispersions of two normal distributions and by the Smirnov test for checking the hypotheses on the equality of two distributions. For checking the significance of the positive trend of the yearly mean temperature, the hypotheses on the significance of the coefficients of the linear regression function by the Student t-statistics and the hypothesis on the linear connection presence by the analysis of variance were checked. As the result, the insignificance of the positive linear trend from 1998 to 2016 and from 1998 to 2017 and its significance from 1998 to 2018 and from 1998 to 2019 on the level of significance 0.05 for mean average yearly atmospheric temperature at the meteorological station Minsk was stated.